2022
DOI: 10.1097/rlu.0000000000004062
|View full text |Cite
|
Sign up to set email alerts
|

New Biomarkers With Prognostic Impact Based on Multitracer PET/CT Imaging in Neuroendocrine Neoplasms

Abstract: The search for new biomarkers in cancer is currently one of the most widely sought end points in medical imaging, with the aim of improving the management decisions based on reliable indicators of prognosis, being neuroendocrine neoplasms a challenging group of tumors under investigation. Multitracer PET/CT imaging, in which different radiotracers supply information of different metabolic aspects of the tumor, can help classify and select the most appropriate therapy, providing basic aspects that will probably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…As such, SSTR-PET negative lesions may still represent higher grade NETs. 12 Finally, the number of patients included in this registry for some sites such the lungs or adrenal glands was small, which limits generalizability of the results for these sites.…”
Section: Biochemical and Clinical Suspicionmentioning
confidence: 99%
“…As such, SSTR-PET negative lesions may still represent higher grade NETs. 12 Finally, the number of patients included in this registry for some sites such the lungs or adrenal glands was small, which limits generalizability of the results for these sites.…”
Section: Biochemical and Clinical Suspicionmentioning
confidence: 99%
“…The introduction in the clinical arena of [ 68 Ga]Ga-FAPI, in addition to those PET radiotracers already available, opens up new diagnostic possibilities in challenging tumors, such as NEN. Multitracer PET/CT imaging, together with clinical features, will provide a setting in which to search for powerful prognostic biomarkers that will help improve the management of these patients 18,19 . In this regard, it is key to promote well-designed and well-performed research, reproducible and harmonized to facilitate comparability, 1 and reach the higher level of evidence and generalizability possible.…”
mentioning
confidence: 99%
“…Studies with FAPI compounds, either [ 68 Ga]Ga-labeled or [ 18 F]F-labeled, have demonstrated three interesting characteristics: (a) favorable pharmacokinetic characteristics and high tumor/background activity, (b) favorable distribution in the liver, and (c) no physiological uptake in the gastric or intestinal mucosa, allowing improved visualization of both primary tumors and peritoneal metastases. [9][10][11] Initial evidence comparing PET/CT with [ 18 F]FDG and [ 68 Ga]Ga-FAPI in patients with gastrointestinal and colorectal cancers showed better diagnostic performance for FAPI-imaging.…”
mentioning
confidence: 99%
“…In the context of management of NETs, it is of main importance to consider clinical factors, as they can offer vital insights for appropriately planning and timing PET/CT examinations or interpreting the results. 7 The advantage of functional imaging compared with other imaging techniques relies on the wide spectrum of available radiotracers 8 that can mimic a so-called in vivo immunohistochemical study and provides some useful prognostic informations such as 18 F-FDG and 68 Ga-SSA uptake patterns for assessing differentiation. Moreover, assessment of somatostatin receptors' status by 68 Ga-SSA is also mandatory from a theranostic point of view for selecting patients who are likely to benefit from peptide-receptor radioligand therapy or PRRT (ie, 177 Lu-SSA).…”
mentioning
confidence: 99%